2018
DOI: 10.1038/s41598-018-22395-6
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils and their components are a class of antifungals with potent vapour-phase-mediated anti-Candida activity

Abstract: Multi-resistant microorganisms continue to challenge medicine and fuel the search for new antimicrobials. Here we show that essential oils and their components are a promising class of antifungals that can have specific anti-Candida activity via their vapour-phase. We quantify the vapour-phase-mediated antimicrobial activity (VMAA) of 175 essential oils and 37 essential oil components, representing more than a 1,000 unique molecules, against C. albicans and C. glabrata in a novel vapour-phase-mediated suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…The results of López et al (2007) indicate, that trans-cinnamaldehyde, the main compound of this oil might be responsible for its antimicrobial activity. Another in vitro experiment of Feyaerts et al (2018) carried out with 175 EOs confirmed the previous observation. The authors' results showed, that the EOs which contain high amount of aldehydes, had the highest inhibitory effect in vapour phase.…”
Section: Introductionsupporting
confidence: 86%
“…The results of López et al (2007) indicate, that trans-cinnamaldehyde, the main compound of this oil might be responsible for its antimicrobial activity. Another in vitro experiment of Feyaerts et al (2018) carried out with 175 EOs confirmed the previous observation. The authors' results showed, that the EOs which contain high amount of aldehydes, had the highest inhibitory effect in vapour phase.…”
Section: Introductionsupporting
confidence: 86%
“…By screening a large collection of essential oils it was shown that ‘paradoxical like phenotypes’ were caused by small volatile molecules released from adjacent wells. This observation led to the development of a quantitative method to evaluate the activity of volatile molecules in the vicinity 59 .…”
Section: Methods For Antifungal Susceptibility Testing Of Planktonic mentioning
confidence: 99%
“…Chemical composition, quality and origin of the EOs were certified by the company. The reduction from 188 EOs to our final set of 175 is essentially due to deduplication 54 . EOs were considered different when originating from (i) other plant species, (ii) the same plant species but from other plant parts, (iii) the same plant species but a different chemotype, and (iv) certified-organic versus conventional cultivation.…”
Section: Materials and Methods Essential Oils (Eos)mentioning
confidence: 99%
“…The detection of organophosphorus and organochlorine pesticides residue levels was in compliance with the relevant EU-legislation and maximum permitted levels were never exceeded 56 . The chemical composition (≥10%) and metadata of the EOs used in this study was reported previously; see www.nature.com/articles/s41598-018-22395-6 under the heading electronic supplementary material 54 . More detailed analysis certificates and the methodology used (in French) can be consulted at www.inula-group.com/fr/pranaquality (see also SI 1).…”
Section: Materials and Methods Essential Oils (Eos)mentioning
confidence: 99%